Metode Euler-Milstein untuk Solusi Numerik Persamaan Diferensial Stokhastik Ornstein-Uhlenbeck - Taufik Iqbal; Muhammad Subhan (UNIVERSITAS NEGERI PADANG, 2020)
Abstract —The Ornstein-Uhlenbeck.equation is a stochastic differential equation, this equation.is often used in the financial mathematical model. However, to find the solution the Ornstein-Uhlenbeck equation.is.difficult.to complete analytic so it can also be solved by looking for numerical solutions. To get a better numeric solution it is required a numeric. method by. looking at converged. The purpose of the study is to examine. the Euler-Milstein method formula for the solution of the Ornstein-Uhlenbeck equation, shows that numerical solution of Ornstein-Uhlenbeck equation that resulted by Euler-Milstein.method has strong convergence. to exact solutions and create an algorithm to find the solution of Ornstein-Uhlenbeck equation with the Euler-Milstein method. Keywords — stochastic.differential.Equations, ornstein-uhlenbeck equation, euler- milstein method